PENGARUH PENDIDIKAN DAN PELATIHAN, KOMPETENSI TERHADAP KINERJA KARYAWAN PT. BANK RIAU KEPRI KANTOR PUSAT PEKANBARU - Susi Hendriani; Yulia Efni; Arika Fitriani (PEKBIS, 2013)
The purpose of the study was to analyze the effect of education and training towardperformance, the effect of competence toward performance, and the effect ofeducation and training toward competence, and the effect of education and trainingtoward performance which is mediated by competence. This research wasconducted at PT Bank Riau Kepri Cabang Kantor Pusat Pekanbaru with 65 officersas the samples of the research. Path Analysis was used to analyze the researchdata. The research results showed that (1) Education and training variableinfluences significantly 0.379 toward performance, (2) Competence variableinfluences significantly 0.385 toward performance, (3) Education and trainingvariable influences significantly 0.397 toward competence, (4). Education variableinfluences significantly 0.535 toward performance which is mediated bycompetence.Keywords: education and training, competence and performance